Implementasi Metode An-Nahdiyah dalam Pembelajaran Al-Qur’an di TPQ Riyadlotul Uqul Kecamatan Kras Kabupaten Kediri - Fadlilatul Munawaroh; Ika Rosyidatul Fauziyah; Mayla Cindy Carmeliasari; Miftahul Zannah; Moh. Iklil Albahij; Zainal Muttaqin; Abdul Mujib; Fitria Ikhrimadhani (Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2024)
There are various methods for reading the Koran, one of which is the an-Nahdliyah method. The Al-Qur'an learning at TPQ Riyadlotul Uqul also applies this method in teaching the Al_Qur'an to children. The method used in this service is the PAR (Participation Action Research) method, which involves researchers and the people involved to be able to take advantage of the existing research process and contribute fully during the research. The results of this research show that the use of the An-Nahdliyah method is quite effective in providing guidance and learning the Qur'an to children, because the method is fun, not boring, and uses classical stick tapping, and the application of the an-Nahdhiyah method is carried out in 3 (3) ways. three) stages, namely the stage of recognizing letters, the stage of understanding beats as a reading murottal, and the stage of reading together.